Serum assisted PD-L1 aptamer screening for improving its stability - Yu Zhou; Haozhe Zhang; Yujing Ding; Changyuan Yu; Hao Li (Scientific Reports)
Abstract Aptamers have shown potential for diagnosing clinical markers and targeted treatment of diseases. However, their limited stability and short half-life hinder their broader applications. Here, a real sample assisted capture-SELEX strategy is proposed to enhance the aptamer stability, using the selection of specific aptamer towards PD-L1 as an example. Through this developed selection strategy, the aptamer Apt-S1 with higher binding affinity and specificity towards PD-L1 was obtained as compared to the aptamer Apt-A2 which was screened by the traditional capture-SELEX strategy. Moreover, Apt-S1 exhibited a greater PD-L1 binding associated conformational change than Apt-A2, indicating its suitability as a biorecognition element. These findings highlight the potential of Apt-S1 in clinical applications requiring robust and specific targeting of PD-L1. Significantly, Apt-S1 exhibited a lower degradation rate in 10% diluted serum or pure human serum, under the physiological temperature and pH value, compared to Apt-A2. This observation suggested that Apt-S1 possesses higher stability and is more resistant to damage caused by the serum environmental factors, highlighting the superior stability of Apt-S1 over Apt-A2. Furthermore, defatted and deproteinized serum were used to investigate the potential reasons for the improved stability of Apt-S1. The results hinted that the pre-adaptation to nucleases present in serum during the selection process might have contributed to its higher stability. With its improved stability, higher affinity and specificity, Apt-S1 holds great potential for applications in PD-L1 assisted cancer diagnosis and treatment. Meanwhile, the results obtained in this work provide further evidence of the advantages of the real capture-SELEX strategy in improving aptamer stability compared to the traditional strategy.